2004
DOI: 10.1259/dmfr/17777906
|View full text |Cite
|
Sign up to set email alerts
|

Quality of film-based and digital panoramic radiography

Abstract: It was concluded that digital panoramic radiographs are equivalent to film-based images for most purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 22 publications
2
25
0
3
Order By: Relevance
“…Comparisons of film-based and digital radiography were performed previously and visualization of anatomical structures was reported to be worse in digital images than in film images (7). However, this study showed that the digital panoramic radiographs showed sufficient accuracy with a minimum of 119.4% and a maximum of 130.8%, which supports the finding from conventional e665 Table 2.…”
Section: Discussionsupporting
confidence: 73%
“…Comparisons of film-based and digital radiography were performed previously and visualization of anatomical structures was reported to be worse in digital images than in film images (7). However, this study showed that the digital panoramic radiographs showed sufficient accuracy with a minimum of 119.4% and a maximum of 130.8%, which supports the finding from conventional e665 Table 2.…”
Section: Discussionsupporting
confidence: 73%
“…This finding is in line with the general conclusions of many studies reporting equal diagnostic capacity of conventional panoramic films and unfiltered panoramic images. 2,3,6 On the other hand, superiority of film images was observed for the visualization of low-contrast structures.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Studies using panoramic images have compared the quality of unfiltered digital images with films, evaluated the effect of dose reduction on the detection of anatomical structures and/or dental pathologies or compared the performance of different panoramic receptors. [4][5][6][7] It is well known that radiographic recognition of disease requires superior radiographic appearance of normal anatomy. For this purpose, the processing of digital images with the aid of various filters is recommended to produce a ''conventional look'' while overcoming the limitations of conventional film radiography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the digital method has other advantages such as: the elimination of the chemical developing process, the immediate availability of the image, the image enhancement function (mostly changes of density and contrast), the small storage space needed, the use in teleradiology, the availability in multiple reprints, and the lower contamination of the environment [11,13,21,28].…”
Section: Discussionmentioning
confidence: 99%